2015
DOI: 10.5194/gi-4-197-2015
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-plume fibre optic tracking (T-POT) test for flow velocity measurement in groundwater boreholes

Abstract: Abstract. We develop an approach for measuring in-well fluid velocities using point electrical heating combined with spatially and temporally continuous temperature monitoring using distributed temperature sensing (DTS). The method uses a point heater to warm a discrete volume of water. The rate of advection of this plume, once the heating is stopped, equates to the average flow velocity in the well. We conducted thermal-plume fibre optic tracking (T-POT) tests in a borehole in a fractured rock aquifer with th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…In A‐DTS, the cable [e.g. Read et al ., ; Coleman et al ., ; Hausner et al ., ], borehole fluid [e.g., Leaf et al ., ; Read et al ., ], or surrounding rock formation is heated [ Bakker et al ., ]. The temperature response at some or all points during this process is then indicative of either the lithology, ambient groundwater flow, or in‐well flow, and depends closely on how the cable is deployed in the borehole and the nature of the thermal disturbance.…”
Section: Dts Monitoring In Active Mode (A‐dts)mentioning
confidence: 99%
See 3 more Smart Citations
“…In A‐DTS, the cable [e.g. Read et al ., ; Coleman et al ., ; Hausner et al ., ], borehole fluid [e.g., Leaf et al ., ; Read et al ., ], or surrounding rock formation is heated [ Bakker et al ., ]. The temperature response at some or all points during this process is then indicative of either the lithology, ambient groundwater flow, or in‐well flow, and depends closely on how the cable is deployed in the borehole and the nature of the thermal disturbance.…”
Section: Dts Monitoring In Active Mode (A‐dts)mentioning
confidence: 99%
“…Electrical heating can be carried out along the entire or part of the length of the borehole or at point locations. Point heating can be achieved using small heating elements [ Sellwood et al ., ; Read et al ., ]. Uniform heating over lengths of borehole can be achieved with Joule heating along an electrical conductor [ Kurth et al ., ].…”
Section: Dts Monitoring In Active Mode (A‐dts)mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, identification of active fractures under ambient flow conditions is much improved when the water column in the borehole is subjected to a rapid heating episode. DTS can also monitor heat movement and rate of heat dissipation due to vertical flow inside an open borehole, which can be used for locating transmissive fractures and for determining water flow rates in the borehole (Banks et al, 2014;Freifeld et al, 2008;Hurtig et al, 1994;Leaf et al, 2012;Read et al, 2015Read et al, , 2014Sakaguchi & Matsushima, 2000;Sellwood et al, 2015bSellwood et al, , 2015aYamano & Goto, 2005). However, Pehme et al (2010) clearly showed that open-hole temperature profiles can mask many active fractures and it is well-known that hydraulic cross connection can alter the natural flow conditions of an aquifer.…”
Section: Introductionmentioning
confidence: 99%